Supervisory acceleration of convergence for homogeneous systems. Issue 11 (2nd November 2018) - Efimov, D.; Levant, A.; Polyakov, A.; Perruquetti, W.
ABSTRACT: The rate of convergence to the origin for a chain of integrators stabilised by homogeneous feedback is accelerated by a supervisory switching of control parameters. The proposed acceleration algorithm ensures a fixed-time convergence for otherwise exponentially or finite-time stable homogeneous closed-loop systems. Bounded disturbances are taken into account. The results are especially useful in the case of exponentially stable systems widespread in practice. The proposed switching strategy is illustrated by computer simulation.